Trait evolution in tropical rubber (Hevea brasiliensis) trees is related to dry season intensity. (20th September 2018) - Rungwattana, Kanin; Kasemsap, Poonpipope; Phumichai, Thitaporn; Kanpanon, Nicha; Rattanawong, Ratchanee; Hietz, Peter
Abstract: Drought shapes the distribution and survival of trees even in tropical wet forests, and the wood and leaf trait spectra are used to understand drought adaptations. However, trait variation may result from ontogenetic adjustment or be related to tree size and not reflect evolutionary adaptations. Intraspecific variation in adaptations to drought can be an important factor in a species' distribution and response to climate change, but excluding potentially confounding factors and proving adaptive evolution are challenging. Provenance trials can identify hereditary variability. We analysed wood and leaf traits in rubber ( Hevea brasiliensis ) tree clones from 15 locations in the Amazon basin that were planted in northern Thailand, controlled for tree size, tested for genetic relatedness and the phylogenetic signal in traits and compared trait variations with the climate at the location of origin. Correlations between traits and tree size were low. Intraspecific trait variation was similar to relationships in published among‐species comparisons, and correlations among wood traits and correlations among leaf traits were stronger than between wood and leaf traits. Genotype explained 30%–70% of the trait variation, and traits differed in how much of this variation was controlled by location or the relatedness among clones. There was no correlation with mean temperature or total annual rainfall. However, rainfall in the driest quarter (19–199 mm) was strongly related to leaf mass per area, carbon isotopic composition and area‐based nitrogen content ( r 2 = 0.54–0.70) and weaker to wood traits (vessel density and vessel lumen fraction). Trees from locations with a stronger dry season also had higher growth rates in Thailand. All traits correlating with climate showed a significant phylogenetic signal. We found no evidence of increased drought tolerance, but the trait spectrum and higher growth in trees from drier locations suggest that deciduous rubber trees have adapted via drought avoidance rather than tolerance. Our study also underlines the importance of looking at a suite of traits rather than individual ones to understand adaptive strategies. Aplain language summary is available for this article. Abstract : Plain Language Summary